Agricultural waste-based lactic acid production by the fungus Rhizopus oryzae: a tool for sustainable polylactic acid production for agricultural use - a review - Chandra Sekhar Paul; Luka Stefanovic; Tatiana Robledo-Mahón; Filip Mercl; Jiřina Száková; Pavel Tlustoš (Plant, Soil and Environment)
Lactic acid has gained considerable attention globally due to its multi-purpose application. Commercial lactic acid production uses the fungal species Rhizopus oryzae, which produces other organic acids. A crucial point of effective fungal organic acid production is matching the fungal strains' requirements, where the carbon source plays a major role. The highest production rate is achieved when glucose is used as a carbon source. Alternatively, we can apply carbon-rich agricultural residues as carbon sources. Using agricultural waste for lactic acid production provides a sustainable and cost-effective feedstock but also helps to reduce greenhouse gas emissions by diverting waste from landfills and decreasing reliance on fossil fuels. Moreover, polylactic acid (PLA) produced from lactic acid monomers can occur in numerous agricultural applications. We should delve deeper into sustainable methods of using carbon residues to recycle waste, foster the circular economy, and advance sustainable agriculture. Therefore, there is a need for further research on the commercial use of agricultural and food industry wastes for lactic acid production.